A silica-based magnetic platform decorated with mixed ligand gold nanoparticles: a recyclable catalyst for esterification reactions. Issue 32 (29th March 2016) - Ertem, Elif; Murillo-Cremaes, Nerea; Carney, Randy Patrick; Laromaine, Anna; Janeček, Emma-Rose; Roig, Anna; Stellacci, Francesco
Abstract : We have developed hierarchical Fe2 O3 @SiO2 @Au nanospheres and we have demonstrated their use as efficient and easily recoverable catalysts in the conversion of benzyl alcohol to benzyl acetate. Abstract : A novel and convenient synthetic strategy for the preparation of magnetically responsive silica nanospheres decorated with mixed ligand protected gold nanoparticles is described. Gold nanoparticles are attached to the silica surface via stable amide bond formation. The hierarchical nanospheres show promising results as reusable and efficient catalysts for esterification reactions and they can be recovered through a simple magnetic separation.